2018
DOI: 10.1007/s00464-018-6116-1
|View full text |Cite
|
Sign up to set email alerts
|

The safe use of surgical energy devices by surgeons may be overestimated

Abstract: Surgeons and surgical trainees both have a significant knowledge gap in the safe and effective use of surgical energy devices, regardless of surgical specialty and despite what they feel was adequate training. The knowledge gap is not improved with experience. A formal surgical energy education program should be a requirement for residency training or credentialing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Early high-frequency electric knives primarily utilized spark gap discharge mechanisms, relying on capacitors, inductors, and adjustable spark electrodes. They generated arc sparks through high alternating current voltage, pos-ing a significant risk of burn accidents and carrying substantial inherent risks [9]. With the development of semiconductor technology, high-frequency electric knife devices gradually transitioned to utilizing semiconductor technologies such as transistors and metal-oxide-semiconductor field-effect transistors, coupled with high-frequency sinusoidal waves with lower harmonic components as the output waveform.…”
Section: Development Of Electrosurgerymentioning
confidence: 99%
“…Early high-frequency electric knives primarily utilized spark gap discharge mechanisms, relying on capacitors, inductors, and adjustable spark electrodes. They generated arc sparks through high alternating current voltage, pos-ing a significant risk of burn accidents and carrying substantial inherent risks [9]. With the development of semiconductor technology, high-frequency electric knife devices gradually transitioned to utilizing semiconductor technologies such as transistors and metal-oxide-semiconductor field-effect transistors, coupled with high-frequency sinusoidal waves with lower harmonic components as the output waveform.…”
Section: Development Of Electrosurgerymentioning
confidence: 99%
“…Significant knowledge gaps exist in all surgical specialties regarding safe use of surgical energy and response to fires 7,8,16,38,39 . For orthopaedic surgeons specifically, Jardaly et al reported that 47.7% of orthopaedic surgeons did not have any formal training on fire prevention and response 16 .…”
Section: Education and Trainingmentioning
confidence: 99%
“…It is critical that the surgeon, anesthetist, and staff know how to react quickly and decisively to limit the damage. Recent articles have shown substantial gaps in resident and staff training in safe use of electrocautery and how to react when a fire starts and called for codified training 7 . Programs such as the Fundamental Use of Surgical Energy (FUSE) curriculum and Virtual Electrosurgical Skill Trainer (VEST) system developed by the Society of American Gastrointestinal and Endoscopic Surgeons have shown good promise in surgeon education and training; however, they are not widely implemented 8-10 .…”
mentioning
confidence: 99%
“…Technological improvements and developments of new devices are likely to continue. There is not enough contemporary information about new technologies in the current medical and residency education curriculum [54]. To address this gap, the Fundamental Use of Surgical Energy (FUSE) program was designed by a multidisciplinary team of doctors, engineers, nurses, and educators.…”
Section: Complicationsmentioning
confidence: 99%